Delineation and Characterization of Waterlogged Salt Affected Soils in Loonkaransar Area of IGNP for Reclamation and Management - Mandal, A K; Sharma, R C (Annals of Arid Zone, 2016)
The Indian Remote Sensing (IRS LISS II) data on 1:50,000 scale showed prominent waterlogging as surface ponding in sandy flats and depressions along the Loonkaransar lift canal under the Indira Gandhi Nahar Pariyojona (IGNP). The seasonal data revealed higher extent of waterlogging in February and mixed spectral signatures of high moisture content with poor crop stand in November and permanent waterlogging (close to the lift canal) in June data. Ground truth survey revealed the presence of shallow aquifer (water table depth <1.5 m) condition, patchy crop stand, moist soil profile and soil salinization. The occurrence of fluctuating (1.5-6.0 m) water table depth during dry and wet cycles and poor cop stand in irrigated areas showed the presence of potential waterlogging zones. Moderate to high soil salinity were found at surface soil located in low-lying flats and higher salinity at sub-surface depth (control section, 0.2-0.8 m) of soil profiles indicating initiation of secondary salinization. The layer of calcium carbonate was present at a depth below the surface. The chlorides and sulfates of sodium, calcium and magnesium were dominant salts in the study area. The water quality of drainage effluents was extremely poor and may be used with good quality of water either in cyclic and mixing mode. The quality of ponded and subsurface profile water moderate and are fit for reuse.